Pengalaman hidup ibu dengan riwayat kehamilan preeklamsia di Yogyakarta - Maulida Rahmawati Emha; Elsi Dwi Hapsari; Wiwin Lismidiati (Fakultas Kedokteran Universitas Gadjah Mada, 2017)
Life experience of mother with preeclampsy pregnancy history in YogyakartaPurposeThe purpose of this paper was to determine the life experience of women with pre-eclampsia pregnancy history.MethodsThis research was a phenomenology study involving 7 postpartum mothers with history of pregnancy and delivery of preeclampsia in Dr. Sardjito Hospital conducted from June to September 2015.ResultsBased on this research, there were 4 themes which were found: 1) the symptoms that are felt to affect the psychological, spiritual, physical and behavior of the mother; 2) Awareness raising; 3) Source of power from family and community; and 4) Anxiety and fear have an impact on the mother's perception during the process of referral and childbirth.ConclusionThis study contributes to the knowledge that maternal conditions with preeclampsia pregnancy and childbirth in Yogyakarta still require the attention of health workers, especially from the aspects of alertness to perceived symptoms and the importance of information about pregnancy preeclampsia.